Botulinum neurotoxin type A in the interdisciplinary treatment of sialorrhea in adults and children—update and practice recommendations - Jost, Wolfgang H.; Bäumer, Tobias; Bevot, Andrea; Birkmann, Ulrich; Buhmann, Carsten; Grosheva, Maria; Guntinas-Lichius, Orlando; Laskawi, Rainer; Paus, Sebastian; Pflug, Christina; Schroeder, A. Sebastian; Spittau, Björn; et al. (Frontiers in Neurology, 2023)
Sialorrhea is defined as a chronic excessive flow of saliva from the mouth, often with adverse consequences for health and quality of life of patients. In addition to currently used non-drug treatment and systemic drugs, intraglandular Botulinum Neurotoxin A (BoNT/A) injections have been examined in case studies, controlled trials and clinical practice. Two pivotal Phase III trials recently led to market approval in the USA and EU for IncobotulinumtoxinA [Xeomin®, IncoBoNT/A, Clostridium botulinum neurotoxin type A (150 kD), free from complexing proteins, Merz Pharmaceuticals GmbH] for treatment of chronic sialorrhea in adults and pediatric patients. This review provides a multidisciplinary approach to discuss the current state of sialorrhea therapy as well as benefits and current limitations of BoNT/A injections. A consensus regarding treatment recommendations made available to physicians in Germany in 2022 has now been updated here for presentation to an international audience. This review provides a framework including a flow chart for patient selection, recommendations for dosing and the injection process, as well as a discussion of therapeutic goals, long-term benefits and safety aspects. This review is aimed at supporting physicians in developing multidisciplinary and individualized treatment approaches to achieve optimal benefits for patients.